Sátántangó (1-3 rész) - Tarr, Béla (Hungary : Fehér, György ; von Vietinghoff, Joachim ; Waldburger, Ruth, 1994)
Bela Tarr's seven-hour, black-and-white epic based on the novel by Laszlo Karsznahorkai took two years to film. The complex story follows a group of people living in a dilapidated village in post-communist Hungary. Tarr examines their standstill lives through a series of episodes told from each person's point-of-view.